2015
DOI: 10.1001/jamaoncol.2015.2943
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcome of Colorectal Cancer Liver Metastases in Elderly Patients

Abstract: Resection of CRC LM is associated with greater risk of postoperative mortality among elderly patients despite less aggressive treatment. Although the long-term outcomes are inferior to younger patients, a substantial proportion of elderly patients will have long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 23 publications
3
86
1
2
Order By: Relevance
“…Major hepatectomy was more frequently performed in patients aged <75 years (61%) compared with patients aged >75 years (53%; p  = 0.003). Only 2 studies reported histopathological radicality [28, 29], which showed no differences (90 vs. 89%; p  = 0.45; Table 4). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Major hepatectomy was more frequently performed in patients aged <75 years (61%) compared with patients aged >75 years (53%; p  = 0.003). Only 2 studies reported histopathological radicality [28, 29], which showed no differences (90 vs. 89%; p  = 0.45; Table 4). …”
Section: Resultsmentioning
confidence: 99%
“…The increase in weighted postoperative morbidity and mortality for patients aged >75 years in this study supports this trend; the postoperative mortality almost doubles in patients >75 years. A dozen number of studies use even 65 years or even lesser as a cut-off point [46-49], but other studies select patients over 75 [50, 51] or even over 80 years of age [31, 39, 52]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may avoid costly and/or prolonged chemotherapy regimens or other traditional alternatives that may have significant toxicity with lower quality of life. 21,22 …”
Section: Discussionmentioning
confidence: 99%
“…Current literature regarding treatment decisions for elderly patients with CRC is conflicting. Alongside reports on the benefit of chemotherapy and surgery in elderly CRC patients [3138] , there are data implying a minimal benefit for oxaliplatin in the adjuvant setting [27,39] and a higher treatment complication rate [28,40] in older patients. In this cohort, there was no difference in chemotherapy associated toxicity.…”
Section: Discussionmentioning
confidence: 99%